KOMUNIKASI PERSUASIF DISNAKERTRANS KOTA BOGOR MENGATASI MASALAH PENGANGGURAN GENERASI MILENIAL: Kajian Kualitatif Tentang Komunikasi Persuasif Melalui Media Sosial Instagram Pada Program Pengurangan Pengangguran Di Kota Bogor - Yusuf Hartawan (Linimasa : Jurnal Ilmu Komunikasi, 2020)
ABSTRACT The purpose of this study was to determine Persuasive Communication conducted by the Bogor City of The Labor and Transmigration Department in implementing the unemployment reduction program through Social Media (Instagram) on Milennial generation. The theory used is the theory of attitude change (Attitude Change Theory) from Carl Hovland. This theory builds a rationale (Ground Work) regarding the relationship between communication stimuli, audience self tendencies and changes in opinion from Instagram users. This research uses qualitative research methods with visual ethnographic studies through direct (reality) and detailed observation through online. In determining the informants or research subjects selected from participants based on the activity of Instagram users, especially job seekers represented by seven people and three employees of Bogor City of The Labor and Transmigration Department. Data collection techniques were obtained through in-depth interviews online, then the data obtained were compiled and coded in the source triangulation stage as validity. The results of research at the Bogor City of The Labor and Transmigration Department with the unemployment reduction program through Social Media Instragram produced a good response from users, especially Milennial job seekers with many becoming Followers. Persuasive communication conducted by the Bogor City of The Labor and Transmigration Department by inviting and changing the opinions of its Followers resulted in the number of job seekers who have gotten work, thereby reducing the number of unemployment, meaning reduction in unemployment in the City of Bogor including the Bogor City of The Labor and Transmigration Department program which is considered successful.